Queer Coding dalam Squid Game: Analisis Teori Semiotika dan Queer terhadap Subteks LGBTQ+ yang Tersembunyi - Arfiani, Anindya; Kertamukti, Rama; Ahmad Dio Putra Fatikha Rizky; Muhammad Kamal Kharrazi; Syefira Maharani Tasynim (Jurnal Pewarta Indonesia, 2025)
This research analyzes how the Squid Game series utilizes queer coding as a semiotic strategy to insert LGBTQ+ representations in the context of South Korean culture which is still dominated by heteronormative norms. Using a qualitative approach and visual semiotic analysis based on the theories of gender performativity (Butler), cultural myth (Barthes), and the concept of representation (Stuart Hall), this study identifies four forms of queer coding: predatory aesthetics, ambivalent queer heroism, gender ambiguous bodies, and symbolic resistance. The findings show that queer coding in Squid Game is ambivalent and can challenge patriarchal norms, while simultaneously reproducing stereotypes and deviance. The analysis also reveals that queer coding operates in a tug-of-war between political resistance, global market demands, and local cultural censorship. This research contributes to the global discourse on LGBTQ+ representations in non-Western popular media, and opens up space for critical reflection on how queer aesthetics are commodified in contemporary entertainment capitalism.